Falsely Increased Plasma Lactate Dehydrogenase without Hemolysis Following Transport through Pneumatic Tube System. (19th November 2019) - Herman, Daniel S; Toro, Esmeralda; Baraban, Ezra G; Bagg, Adam; Wang, Ping
Abstract: Background: Lactate dehydrogenase (LDH) is a nonspecific biomarker for diseases including lymphoma. Serum and plasma are generally considered interchangeable for LDH testing. Investigation into falsely increased plasma LDH concentration results led to the hypothesis that a workflow change that included pneumatic tube system (PTS) transportation caused the errors. The following study was conducted to test the hypothesis. Methods: Plasma and serum separator tube samples were each drawn in duplicate, centrifuged, transported either through the PTS or by hand courier, and evaluated by means of clinical chemistry and hematology assays. Smear slides were made out of the plasma and examined. Aggregate patient results before and after the PTS workflow change were compared. Results: In post-PTS plasma samples, LDH activity was 26%–149% higher. Similarly, white blood cells (WBCs) were 14- to 156-fold higher and platelets were 1- to 13-fold higher. Smear examination revealed dramatically more cells and cell fragments. No significant hemolysis was observed in plasma by chemistry hemolysis indices or hemoglobin testing. These effects were not observed in similarly transported serum samples in gel separator tubes. Aggregate LDH patient results, including moving medians, demonstrated dramatic changes following PTS workflow implementation. Conclusions: PTS transportation led to falsely increased LDH concentration in plasma. These LDH concentration elevations are not heralded by standard indicators of hemolysis. These errors can be prevented by restricting LDH concentration testing to serum collected in gel separator tubes. Moving patient statistics can effectively detect important testing process changes not revealed by external QC or indices.